CONTENT ANALYSIS OF ENGLISH SUBJECT IN CURRICULUM 2013 FOR JUNIOR HIGH SCHOOL LEVELS - Wida Cahyaningrum; Ovie Kholillatus Shofia; Premaria Mahaputri (Getsempena English Education Journal, 2018)
As a framework, curriculum 2013 focuses on four aspects which are religious, attitude, knowledge, and skills. However, there are still confusions among teachers in applying their teaching practices based on it. Thus, this study is designed to provide information of the current framework, curriculum 2013, especially for English subject in junior high school level. Furthermore, it is analysed based on components which appear in the curriculum. The result shows that the curriculum benefits English teachers because of its flexibility and detail components to carry out teaching. It accomplishes the requirements as an integrated framework. It supports a view of using English to learn new knowledge and supports learning integrated skills. In addition, it requires skilful English teachers to carry out teaching and learning processes since it focuses on giving learners real-life experiences in their learning.